A comprehensive evaluation of asphalt concrete modified with ACP based on improved AHP and radar chart method - Bi, Jiefu; Zhang, Qing (Frontiers in Energy Research, 2024)
Microwave heating, as an efficient and environmentally friendly heating technology, is used in solving rapid deicing issues of asphalt pavement. In this study, activated carbon powder (ACP) was adopted to partly replace mineral powder and improve the microwave heating efficiency of asphalt concrete. Some tests of key indexes about deicing, microwave heating, asphalt concrete and asphalt mastic were conducted in laboratory. In order to comprehensively compare and analyze the performance of asphalt concrete at different replacements and recommend the best type of asphalt concrete with laboratory data, an advanced data processing and mathematical model was established based on improved Analytic Hierarchy Process (AHP) and radar chart method. The results show that the fi representing the comprehensive performance of each type of asphalt concrete can be ranked as f6>f5>f4>f3>f2>f1. Therefore, it can be easily recommended that the type of asphalt concrete that meets the expected requirements is that with 100% ACP replacement amount. Additionally, the established model has proved feasible and effective through the application of this research. Finally, this research’s process and results can provide a new idea and reference for resolution of similar problems in the future.